Profile of Chlamydia vaccine research: A bibliometric analysis - Xuemei Wang; Qian Wang; Yidan Gao; Lijuan Jiang; Lingli Tang (Human Vaccines & Immunotherapeutics)
Vaccination is the most effective measure to prevent Chlamydia infection. However, to date, no vaccine has successfully completed the rigorous clinical trial process and gained regulatory approval for use in clinical practice. Scholars have been working on a safe and effective Chlamydia vaccine. In order to better grasp, the global frontiers and development trends in this field, a comprehensive bibliometric analysis was carried out. A total of 234 publications closely regarding Chlamydia vaccines were culled from the Web of Science Core Collection database, and the bibliometric information was then extracted with CiteSpace and VOSviewer software. After measurement analysis, the most influential papers were identified in this area, including highly cited papers, references with strong citation burst, and high co-citated papers. Vaccine has published the most literature on Chlamydia vaccines. Only scholars from 39 countries/regions have been engaged in studying Chlamydia vaccines. The USA is the most prolific country and has the highest collaborative strength. The current research area has focused on protective immunity and immunopathological response. Major outer membrane protein (MOMP) is the most common target vaccine antigen. This study reveals the status of literature and highlights emerging trends in this field, which helps researchers seek insights into this area and serve as a reference guide for further investigations.